Psychological fluency and its relation to psychological flow among students of Physical Education and Sports Sciences - Attwan, Lamyaa Y.; Alkhigani , Aamer S. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2022)
The aim of this study was to identify the psychological fluency and psychological flow and the relationship between them among students of the fourth stage of the College of Physical Education and Sports Sciences at the University of Babylon. A cross sectional study was carried out and it was used a descriptive approach with survey and correlational methods. A total of 15 female students participated in the study. Psychological fluency scale and psychological flow scale were used as research instruments to identify the psychological fluency and psychological flow and the relationship between them. After processing the results statistically, we found that the fourth-stage students of the College of Physical Education and Sports Sciences enjoy a high level of psychological fluency and also a high level of psychological flow. Psychological fluency had a positive relationship with the psychological flow as the calculated scores for the correlation relationships were 0.428, 0.422, 0.235 and 0.766. In conclusion, the fourth-stage students of the College of Physical Education and Sports Sciences enjoy a high level of psychological fluency and psychological flow. Psychological fluency had a positive relationship with the psychological flow of fourth-stage students in the College of Physical Education and Sports Science, with a high level of psychological fluency.